TOTAL QUALITY MANAGEMENT IN PROMOTING SUPERIOR MADRASAH IN STATE MADRASAH ALIYAH 2 PAYAKUMBUH - Tiara Rapika Duri; Idarianty; Mahmud MY (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
Total quality management is oriented towards the interests and needs of users. Therefore it is a strategic choice in managing and providing the best service to every user. This article seeks to explore how the school principal's policy in using total quality management for the realization of superior madrasas at Madrasah Aliyah Negeri 2 Payakumbuh. MAN 2 Payakumbuh which has obtained accreditation A has shown its contribution to learning through strategic policies and flagship programs. This research utilizes qualitative methods. Using observation, interviews and documentation in data collection. As well as conducting analysis with data reduction techniques, data display, and data verification. This article finds that the principal's policy, especially in the flagship program, has shown good results and responses from users. The school principal realizes total quality management in terms of school policies, especially in academic and non-academic programs. In addition, MAN 2 Payakumbuh has been awarded as a child-friendly school and favorite Islamic school in terms of quality of education by President Joko Widodo. These results can be expressed as the implementation of total quality that works in realizing superior madrasas.